Selecting for stable and productive families of eucalyptus urophylla across a country-wide range of climates in Brazil - da Silva, Paulo Henrique Müller [UNESP]; Brune, Arno; Alvares, Clayton Alcarde; Amaral, Weber Do; de Moraes, Mario Luiz Teixeira [UNESP]; Grattapaglia, Dario; de Paula, Rinaldo Cesar [UNESP] (Canadian Science Publishing, 2019)
To identify stable and productive Eucalyptus urophylla S.T. Blake families across diverse climate zones in Brazil, we evaluated growth and survival of 322 open-pollinated families derived from 13 genetically improved seed sources in 10 trials across the country. Survival and growth data were analyzed using linear mixed models and REML/BLUP. Survival ranged from 51% to 92%, and the mean annual increment varied from 19 to 46 m 3 ·ha −1 ·year −1 . Although planted in suitable climatic zones, some trials had low survival and (or) productivity. Conversely, the highest productivity was recorded in a zone considered to be of low suitability. These results show the importance of assessing the climatic requirements of eucalypts beyond those determined from analyses of their natural distribution, especially when testing already improved seed sources. A number of productive and stable families were identified based on analysis of the interaction between genotype and environment, and from these, 144 individuals were selected and had their genetic diversity estimated using 19 microsatellite DNA markers. The genetic diversity of these selected trees was equivalent to that observed in previous studies of natural populations of E. urophylla, indicating that breeding programs of E. urophylla in Brazil still retain high levels of diversity for sustainable genetic gains.
Keywords: Abiotic and biotic stress; Family selection; Genetic diversity; Genotype-environment interaction; Productivity and stability